Navigating multi-locality in rural-urban and return migration: a study of young migrant mothers' experience in Beijing - Bao, Rong (Trinity College Dublin. School of Social Work & Social Policy. Discipline of Social Studies, 2023)
During the past decades, China has witnessed one of the biggest waves of rural-urban migration in human history. Despite the ever-rising prevalence, theorisation of rural-urban migration still largely lacks specification and contextualisation. Traditionally, studies of rural-urban migration in China tend to focus on institutional barriers shaping or even defining the migration experience, and explaining how and why rural migrants are struggling at the bottom of urban society. Female migrants are especially marginalised, often portrayed either as victims with inherent vulnerability or as passive associate migrants in family migration projects. Studies about migrant mothers are even more scant, mostly referring to mothers who migrate and leave their child behind. The few studies that look at the migrant mothers who raise the child in the destination city tend to portray them as homogeneous and lacking agency. Most explore female rural-urban migration from a `top-down' perspective, and a focus on experience is largely missing. Moreover, most existing migration theories are developed by the western scholars based on research of international migration in western contexts, and therefore may not be able to provide a contextualised understanding of rural-urban migration in China, which is deeply rooted in the specific structural and cultural environment. To generate a more specified and contextualised understanding of female rural-urban migration in contemporary China and capture its complexity this study adopts a Constructivist Grounded Theory approach, which is interactive, abductive and reflexive. It generates rich empirical data of young migrant mothers? lived experience of rural-urban migration, which is the basis from which to propose a grounded theorisation of this process. This study starts by asking one big question, `What is it like to be a young migrant mother in Beijing?' It seeks to answer it based on qualitative, experience orientated interviews with twelve rural migrant mothers, aged 18-28, who were living with their child in a migrant village in peripheral Beijing including follow-up interviews with seven of the twelve women one year after their first interview. The study reveals that the migrant women in this study actively perform adaptive agency to navigate a multi-local life world via multi-directional flows of capabilities and aspirations to fulfil multi-local familial relationships. During this process, the migrant women also develop a multi-local identity, which in turn shapes their understanding and performance of migratory agency. All these processes intersect and create the multi-local space that the migrant women have to navigate on a daily basis. The multi-locality framework is grounded in the empirical data of the study and builds on transnationalism theories and de Haas' (2021) Aspirations-Capabilities Approach. It further develops the concept of multi-locality in livelihood research. It suggests that multi-locality can be understood as the lived experience of migration itself, rather than a mere livelihood strategy. It also demonstrates how return migration should be understood as an integral part of the overall migration process, and how the changing aspirations for return migration shape and reshape the multi-local space. This study brings the Chinese context into the theoretical conversation by incorporating the Chinese construct of family, agency and gender in the process of data analysis and theory development to unravel how agency, family and gender interact and intersect in the migration process and further complicate the migration experience. This study proposes a new perspective for understanding female rural-urban migration and points out potential directions for future research, which will ultimately advance the theorisation of rural-urban migration.
APPROVED
Keywords: rural-urban migration; female migration; return migration; migration in China; migrant motherhood